The Influence Of Health Counseling On The Level Of Community Knowledge Regarding The Eradication Of Mosquito Nests (Psn) And Lents In Gampong Lam Teungoh, Peukan District, Banda Aceh - Putri, Rosalia; Firdaus, Muhammad; Azhar, Firman; Mukminati, Mayasirul; Sopia, Nadia; Suriyatun, Suriyatun (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2023)
Community behavior regarding Dengue Hemorrhagic Fever (DHF) and behavior of eradicating mosquito nests (PSN) is one of the risk factors for the occurrence of DHF. Behavior is influenced by knowledge and exposure to information. The type of research is quantitative and the research method used is pre-experimental design using a one group pretest-posttest design. Of the 50 respondents, the level of public knowledge about eradicating mosquito nests and larvae before being given counseling was 11 respondents (22%) with poor knowledge. and as many as 39 people (78%) with good knowledge. Of the 50 respondents, the level of public knowledge regarding eradicating mosquito nests and larvae after being given counseling, all 50 respondents (100%) had good knowledge. There is an influence of health education on level of community knowledge regarding eradicating mosquito nests and larvae in Gampong Lam Teungoh, Peukan Bada District, Aceh Besar Regency. Counseling will have an impact on knowledge and good knowledge will providegood impact on behavior.